Genetic analysis of lodgepole pine (Pinus contorta) solid wood quality traits - Hayatgheibi, Haleh; Fries, Anders; Kroon, Johan; Wu, Harry (NRC Research Press (a division of Canadian Science Publishing), 2017)
Potential improvement of lodgepole pine (Pinus contorta Dougl. ex Loud. var. latifolia Engelm.) solid wood properties was examined by estimating age trends of inheritance, age-age genetic correlations and the efficiency of early selection using 823 increment cores sampled from 207 half-sib families at two independent progeny trials, aged 34-35 years, located in northern Sweden. High-resolution radial variation of annual ring width, wood density, microfibril angle (MFA) and modulus of elasticity (clearwood stiffness; MOEs) was measured with SilviScan instrument. The dynamic stiffness (MOEtof) of standing trees was also obtained using Hitman ST300. Heritabilities ranged from 0.10 to 0.64 for growth and early-, transition- and latewood proportions, from 0.29 to 0.77 for density traits, and from 0.13 to 0.33 for MFA and stiffness traits. Genetic correlations between early age and the reference age (26 years) suggested that early selection is efficient at age 4 for MFA, and between ages 5 to 8 years for density and MOEs. Unfavorable diameter-stiffness genetic correlations and correlated responses indicate that breeding for 1% increase in diameter would confer 5.5 and 2.3% decreases in lodgepole pine MOEs and MOEtof, respectively. Index selection with appropriate economical weights for growth and wood stiffness is highly recommended for selective breeding. The accepted manuscript in pdf format is listed with the files at the bottom of this page. The presentation of the authors' names and (or) special characters in the title of the manuscript may differ slightly between what is listed on this page and what is listed in the pdf file of the accepted manuscript; that in the pdf file of the accepted manuscript is what was submitted by the author.